2004
DOI: 10.1530/rep.1.00444
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic diapause and its regulation

Abstract: Embryonic diapause, a condition of temporary suspension of development of the mammalian embryo, occurs due to suppression of cell proliferation at the blastocyst stage. It is an evolutionary strategy to ensure the survival of neonates. Obligate diapause occurs in every gestation of some species, while facultative diapause ensues in others, associated with metabolic stress, usually lactation. The onset, maintenance and escape from diapause are regulated by cascades of environmental, hypophyseal, ovarian and ute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
169
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(175 citation statements)
references
References 85 publications
4
169
0
2
Order By: Relevance
“…As a consequence, it helps the species survive extreme forms of stress (e.g., drought) and it also “times” the birth of offspring to a more favorable environment (e.g., rainy season). In nature, diapause phenomena are widespread throughout the animal kingdom, from simple organisms such as brine shrimps and silkworms, to mammals such as the roe deer, bats, and mice (Bleier, 1975; Emerson, Bradshaw & Holzapfel, 2009; Hand, Denlinger, Podrabsky & Roy, 2016; Lambert et al., 2001; Lopes, Desmarais & Murphy, 2004; Meenakumari & Krishna, 2005; Ptak et al., 2012; Sato et al., 2014; Schiesari & O'Connor, 2013; Sim & Denlinger, 2013). Our current knowledge of diapause has benefited greatly from the studies in invertebrates.…”
Section: Using the African Turquoise Killifish As A Research Organismmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, it helps the species survive extreme forms of stress (e.g., drought) and it also “times” the birth of offspring to a more favorable environment (e.g., rainy season). In nature, diapause phenomena are widespread throughout the animal kingdom, from simple organisms such as brine shrimps and silkworms, to mammals such as the roe deer, bats, and mice (Bleier, 1975; Emerson, Bradshaw & Holzapfel, 2009; Hand, Denlinger, Podrabsky & Roy, 2016; Lambert et al., 2001; Lopes, Desmarais & Murphy, 2004; Meenakumari & Krishna, 2005; Ptak et al., 2012; Sato et al., 2014; Schiesari & O'Connor, 2013; Sim & Denlinger, 2013). Our current knowledge of diapause has benefited greatly from the studies in invertebrates.…”
Section: Using the African Turquoise Killifish As A Research Organismmentioning
confidence: 99%
“…Diapause can occur at different developmental stages in diverse species (Hand et al., 2016; Lopes et al., 2004; Mead, 1993; Ptak et al., 2012). In killifishes, diapause can occur during early, intermediate, and late developmental stages (diapause I, II, and III, respectively; Wourms, 1972).…”
Section: Using the African Turquoise Killifish As A Research Organismmentioning
confidence: 99%
“…Indeed, LIF is systematically required when mESCs are grown in combination with two small-molecule inhibitors (referred to as '2i') that block glycogen synthase kinase 3 (GSK3) and mitogen-activated protein kinase kinases (MAP2Ks, also known as MEKs) or when grown in the presence of bone morphogenetic protein (BMP) (Ying et al, 2003;Ying et al, 2008). Importantly, although the role of the LIF signalling pathway is well established in pluripotent cells in vitro, genetic studies have shown that the absence of glycoprotein 130 (gp130) or signal transducer and activator of transcription 3 (STAT3) (Nichols et al, 2001; Takeda et al, 1997) -both of which are necessary for LIF signalling -has no consequence on early mouse development but are required for the diapause stage (reviewed in Lopes et al, 2004). These studies indicate that LIF-dependent mESCs are representative of pluripotent cells of the diapause embryo just before implantation.…”
Section: Signaling Pathways Maintaining Pluripotency In Mescsmentioning
confidence: 99%
“…Ovulation is induced by the presence of males or attempted or successful copulation, and a maturation age is about 8 to 12 months -E-mail: minna.koivula@mtt.fi (Lariviè re, 1999;Ferguson and Lariviè re, 2002). Minks have also delayed implantation, which is an evolutionary strategy to ensure that postnatal development can be completed under more favorable environmental conditions (Lopes et al, 2004). Because minks are photosensitive breeders with induced ovulation, it is possible to manipulate the timing of reproductive cycles by altering photoperiod (Fredberg et al, 2006) and also by date of first exposure to males.…”
Section: Introductionmentioning
confidence: 99%